Modelos não-lineares para crescimento de capital - Noia, Edson Vinícius de Paula (2019)
In this work, we propose and analyse nonlinear mathematical models for capital growth. We approach this subject from two situations: first, the capital and the labor force have a cooperative dynamic; secondly, we assume that the relation capital-labor force is given by a predator-prey type dynamic which the capital feeds on labor force. For this, we make use of delay differential equations for modeling and through adapted numerical analysis for this kind of equations, we were focused on study the fixed points, bifurcations and chaotic regime. Assuming the delay as control parameter, a sistem presented chaos transitions by period doubling.